ANALISIS EKONOMI ISLAM TERHADAP PEMENUHAN UPAH LAYAK TENAGA KERJA INDUSTRI BATIK (Studi Kasus : Sentra Batik Kecamatan Plered Kabupaten Cirebon) - Nono Hartono (Universitas Airlangga, 2019)
Batik industry was an excellent product of Plered that have been set by the Government, especially Cirebon. Cirebon Regency was the largest industrial centers batik in West Java, because many industry batik in Plered and many people worked as batik artisans in Plered. The existence of an industry is expected to have many benefits not only for the manufacturers but also for its workforce. The purpose of this research was (1) Identifying the wages received by the batik industry workforce housing units has met the needs of the eligible. (2) Analyze the Economic Outlook of the Islamic labor waging system unit home batik Subdistrict Plered (3) Composing model waging a be eligible on batik home Sub unit Plered. This research used purposive sampling with population of batik industry is a labor of a home unit. Analytical tool used was Multiple Linear Regression. Results the regression show that factors that influence significantly to levels of wage labor unit home batik industry is a long work day, work experience and operational cost, whereas other variables was not significant. Therefore, to increase the wages in order to acquire the necessary life worthy remuneration models that were eligible on the batik industry, are with a view to the verses that have been described in the Qur'an. Wage system that occurred in the housing unit labor could be said to be in accordance with the provisions of the contract of Ijarah, although the amount is not yet worthy but it is in conformity with the customs and traditions in the society Plered and workers batik housing unit no matter anything, as well as the delay in wages Keywords: Labor Housing Units, Minimum Wage, Multiple Linear Regression, Needs Decent LivingREFERENCESDaniyah, Hamidah. 2013. Pengaruh Dana Pihak Ketiga dan Non Performing Loan Terhadap Penyaluran Kredit (PT.Bank ICB Bumiputera., Tbk). Skripsi. Universitas Pendidikan Indonesia.http://repository.upi.edu/2321/6/S_PEM_0901069_Chapter3.pdf. [2/2/2016]Dinas Perindustrian dan Perdagangan Kabupaten Cirebon. 2011. Jumlah Tenaga Kerja Industri Batik. Cirebon.Hafidh Abdul, R. 2010.Hadis Tentang Waktu Pembayaran Upah (Studi Sanad Dan Matan). Skripsi.Jurusan Tafsir Hadis Fakultas Ushuluddin Studi Agama Dan Pemikiran Islam Universitas Islam Negeri Sunan Kalijaga Yogyakarta. [28/1/2016] Mustofa, Muhammad. 2009. Tinjauan Hukum Islam Terhadap Upah Minimum Pasal 1 Ayat 1 dan 2 dalam PERMENAKERTRANS Nomor: PER-17/MEN/VIII/2005. Skripsi.Universitas Islam Negeri Sunan Kalijaga Yogyakarta.Nasir, Nadia. 2008. Analisa Pengaruh Tingkat Upah, Masa Kerja, Usia Terhadap Produktivitas Tenaga Kerja (Studi Kasus Pada Tenaga Kerja Perusahaan Roko “Djagung Padi” Malang). Skripsi. Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Brawijaya Malang.[28/1/2016]Nazir Moh. 1988. Metode Penelitian, Ghalia Indonesia, Jakarta.Sa’adah, Ai. 2014. Analisis Kelayakan Komponen Kebutuhan Hidup Layak dalam Menggambarkan Pemenuhan Kebutuhan Hidup Pekerja/Buruh di PT ASPEX KUMBONG.Skripsi.Institut Pertanian Bogor. [28/1/2016].Santoso Singgih. 2009. Menguasai Statistik Di Era Informasi Dengan SPSS, Jakarta, PT. Elex Media Komputindo.Sugiyono. 2012. Metode Penelitian Kuantitatif Kualitatif dan R&D, Bandung: Alfabeta.Tjiptoherijanto, Prijono. 2001. Proyeksi Penduduk, Angkatan Kerja, Tenaga Kerja, dan Peran Serikat Pekerja dalam Peningkatan Kesejahteraan. Majalah Perencanaan Pembangunan. Edisi 23.Undang- Undang Dasar Republik Indonesia Nomor 13 Tahun 2003 ayat (4) tentang ketenagakerjaan.Undang- Undang Dasar Republik Indonesia Nomor 13 Tahun 2003 Pasal 88 ayat (1) tentang Kebutuhan Hidup Layak (KHL).